Trends in outcomes of women with myocardial infarction undergoing primary angioplasty—Analysis of randomized trials - Motovska, Zuzana; Hlinomaz, Ota; Aschermann, Michael; Jarkovsky, Jiri; Želízko, Michael; Kala, Petr; Groch, Ladislav; Svoboda, Michal; Hromadka, Milan; Widimsky, Petr (Frontiers in Cardiovascular Medicine, 2023)
Background: Sex- and gender-associated differences determine the disease response to treatment. Aim: The study aimed to explore the hypothesis that progress in the management of STE-myocardial infarction (STEMI) overcomes the worse outcome in women. Methods and results: We analyzed three randomized trials enrolling patients treated with primary PCI more than ten years apart. PRAGUE-1,-2 validated the preference of transport for primary PCI over on-site fibrinolysis. PRAGUE-18 enrollment was ongoing at the time of the functional network of 24/7PCI centers, and the intervention was supported by intensive antiplatelets. The proportion of patients with an initial Killip 3,4 was substantially higher in the more recent study (0.6% vs. 6.7%, p=0.004). Median time from symptom onset to the door of the PCI center shortened from 3.8 to 3.0 hours, p<0.001. The proportion of women having a total ischemic time of 3 hours or less was higher in the PRAGUE-18 (OR [95% C.I.] 2.65[2.03–3.47]). However, the percentage of patients with time-to-reperfusion longer than 6hours was still significant (22.3% vs. 27.2% in PRAGUE-18). There was an increase in probability for an initial TIMI flow of more than 0 in the later study (1.49[1.0–2.23]) and also for an optimal procedural result (4.24[2.12–8.49], p<0.001). The risk of 30-day mortality decreased by 61% (0.39[0.17–0.91], p=0.029). Conclusion: The prognosis of women with MI treated with primary PCI improved substantially with twenty-four/seven regional availability of mechanical reperfusion, performance-enhancing technical progress, and intensive adjuvant antithrombotic therapy. A major modifiable hindrance to achieving this benefit in a broad population of women is the timely diagnosis by health professional services.